(untitled) (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This article examines the theoretical foundations and practical mechanisms for developing environmentally sustainable transport systems. It analyzes the impact of transport infrastructure investments on regional economic development, broader economic and spatial consequences (WEIs and WSIs), as well as international experiences in shaping sustainable transport policies. The study employs modern methodologies such as cost–benefit analysis (CBA), multi-criteria analysis (MCA), accessibility modeling, econometric evaluation methods, and computable general equilibrium models (CGE/SCGE). The results indicate that developing sustainable transport systems requires a comprehensive consideration of environmental, economic, and social factors, which is particularly relevant in the context of Uzbekistan, specifically in the case of Khorezm region.